Medical and surgical aspects of weight recurrence after bariatric surgery - Pintar, Tadeja (Surgery and surgical endoscopy, 2023)
Obesity is a chronic, progressive disease with a tendency to recidivism regardless of the type of excessive weight loss, which has been presented through clinical studies. Bariatric and metabolic surgery (MBS) is the most efficacious and durable intervention for morbid obesity and metabolic syndrome, with unique perspectives on T2DM treatment. Prevalence and predictors for insufficient weight loss and recurrence after bariatric surgery (MBS) are complex. Risk factors related to weight recurrence (WR) fall into five categories: anatomical, genetic, dietary, psychiatric, and temporal. Energy restriction initiates powerful compensatory mechanisms to resist weight loss and defend the higher body weight. MBS alters the secretion profile of hormones involved in regulating hunger and satiety. At the same time, it influences long-term weight maintenance through caloric and content restriction after surgery related to weight maintenance and weight recurrence. The gap between observed and predicted energy expenditure after massive weight loss represents metabolic adaptation; a greater metabolic adaptation could be partly responsible for a lower weight loss after surgery. Prevention and treatment strategies should be implemented in clinical management MDT protocols, including protocols for medical preoperative metabolic improvement to reduce perioperative and late postoperative complications, including weight recurrence. Many patients experience significant WR during long-term followup attributed to anatomic and surgical causes. Adjuvant pharmacotherapy can help treat weight recurrence after bariatric surgery. As an adjunct to lifestyle modification might induce clinically meaningful weight loss related to metabolic improvement and reduction of de-novo presentation of obesity-related comorbidities. Technical complications of the surgery or failure of the surgical method can cause WR after BMS. Identifying the cause is the basis for selecting the treatment algorithm with revision surgical and endoscopic interventions and pharmacotherapy.
Keywords: anti-obesity medications; bariatric surgery; bariatrična operacija; behavior therapy; debelost; insufficient weight loss; management; mechanisms of weight regain; mehanizmi za povrnitev telesne teže; napovedovalci; nezadostna izguba teže; obesity; ponovitev teže; predictors; upravljanje; vedenjska terapija; weight recurrence; zdravila proti debelosti